2006 IEEE International Conference on Multimedia and Expo 2006
DOI: 10.1109/icme.2006.262455
|View full text |Cite
|
Sign up to set email alerts
|

PAC DSP Core and Application Processors

Abstract: This paper provides an overview of the Parallel Architecture Core (PAC) project led by SoC Technology Center of Industrial Technology Research Institute (STC/ITRI) in Taiwan. The background of PAC project, a brief introduction to PAC core technologies, PAC SoC development suite, PAC benchmarks, and applications are presented. The main objective of the PAC development plan is to enhance industrial development competitiveness in the core technology related to key components, especially for portable multimedia ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…The distributed and ping-pong register file organization used in PAC DSP are demonstrated to have 76.8% silicon area and 46.9% access time improvement comparing with its equivalent centralized register files [10]. It was reported that the DSP with such register file organization could achieve comparable performance with state-of-the-art DSPs for popular DSP kernels [4,10], which implies that lower power consumption is expectable due to the much less silicon area. This also reveals the importance of a good code generation strategy.…”
Section: Irregular Register Files and Access Constraintsmentioning
confidence: 99%
See 1 more Smart Citation
“…The distributed and ping-pong register file organization used in PAC DSP are demonstrated to have 76.8% silicon area and 46.9% access time improvement comparing with its equivalent centralized register files [10]. It was reported that the DSP with such register file organization could achieve comparable performance with state-of-the-art DSPs for popular DSP kernels [4,10], which implies that lower power consumption is expectable due to the much less silicon area. This also reveals the importance of a good code generation strategy.…”
Section: Irregular Register Files and Access Constraintsmentioning
confidence: 99%
“…This article describes a novel register allocation scheme for a clustered VLIW DSP, known as a Parallel Architecture Core (PAC) DSP [3,4,12,13], which is designed with distinctively banked register files in which port access is highly restricted. The PAC DSP employs a heterogeneous design comprising a single scalar unit (for simple arithmetic, address calculation, and program flow control), plus two data-stream processing clusters, each containing a pair of load/store units and ALU/MAC units with powerful SIMD (Single Instruction stream, Multiple Data stream) capabilities; each unit in the clusters can utilize three types of register file, providing different accessing methods and constraints, and the scalar unit has its own accessible register file.…”
Section: Introductionmentioning
confidence: 99%
“…The PAC project [1][2][3] was initiated in 2003 and executed by Industrial Technology Research Institute (ITRI) [4] in Taiwan, of which the target is to provide a fully-programmable solution for next-generation media-rich and multi-function portable devices, such as portable media players and smart phones. The speech, audio, image and video processing on these devices demand extremely high computing power under tight power constraints.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we present methods to enable streaming RPC flow to support streaming-function off-loading on asymmetric dual-core architectures, which is applicable to both on PAC [13,14] dual-core platforms and TI OMAP dual-core environments. The concept of streaming RPC provides several advantages.…”
Section: Introductionmentioning
confidence: 99%